1987
DOI: 10.1007/bf00853602
|View full text |Cite
|
Sign up to set email alerts
|

Vesico-uretero-renal reflux and the kidney

Abstract: The most frequent complications of non-obstructive vesico-uretero-renal reflux (VUR) are segmental renal scars. These scars are confined to segments with intrarenal reflux which are, in addition, exposed to bacterial infection. Primarily, only gaping collecting duct orifices, confined to compound papillae and mainly situated at the kidney poles, allow intrarenal reflux. Scar contraction and obstruction seem to be able to transform closed collecting duct orifices into gaping ones, thereby enlarging the parenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
5

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 59 publications
0
6
0
5
Order By: Relevance
“…Recent prospective studies have shown that parenchy mal damage can be prevented by long-term chemopro phylaxis or a reflux operation [1][2][3]. The outcome of conservative therapy, however, depends on strict chemo prophylaxis until the disappearance of VUR is con firmed radiologically.…”
Section: Introductionmentioning
confidence: 99%
“…Recent prospective studies have shown that parenchy mal damage can be prevented by long-term chemopro phylaxis or a reflux operation [1][2][3]. The outcome of conservative therapy, however, depends on strict chemo prophylaxis until the disappearance of VUR is con firmed radiologically.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, when the flow of urine is obstructed in the developing kidney a series of abnormalities occur including (1) arrest of glomerular maturation, (2) glomerulosclerosis, (3) ischemia and necrosis of some tubular cells, (4) apoptosis of other tubular and collecting duct cells, (5) interstitial inflammation, proliferation, and fibrosis, and (6) tubular dilatation and atrophy [4–6]. In addition, in animals and humans there is evidence that scarring occurs in compound papillae where intrarenal reflux is present [7]. In humans, RN is usually identified as renal scarring as defined on dimercaptosuccinic acid (DMSA) scan in a patient known to have VUR.…”
Section: Renal Pathophysiology In Reflux Nephropathymentioning
confidence: 99%
“…The renal scarring associated with vesicoureteral reflux (VUR) and urinary tract infection in childhood is one of the [1,2]. Some of the renal changes associated with reflux are developmental and are present from birth, but a proportion are acquired after urinary infection and, therefore, are preventable [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Reflux nephropathy has been shown to be associated with significant renal tubular dysfunction [1,6]. Renal tubular damage mediated by VUR may be manifested by increased levels of renal tubular enzymes.…”
Section: Introductionmentioning
confidence: 99%